The impact of personal attitudes toward successful levels of income for Sahabat in Amanah Ikhtiar Malaysia at Kuala Lumpur / Nur Afeeqah Mohd Zaimi - Mohd Zaimi, Nur Afeeqah (2015)
Amanah Ikhtiar Malaysia (AIM) is a Non-Government Agency (NGO) that was established to help the poor household by providing loans to undertake income generating projects. Entrepreneur whom make loans under AIM are called Sahabat. AIM had detected that some of their Sahabat are wrongly use the loan given. They use it for personal loan rather than for their projects. Thus, this research is to study on how personal attitudes will impact the successful levels of income for Sahabat in Amanah Ikhtiar Malaysia at Kuala Lumpur. The objective of this study is to identify the successful level of income for Sahabat, to identify relationship of personal attitudes in determination toward the successful level of income, to identify the most dominant factors of determination toward the successful level of income and to identify alternatives for continuous improvement toward the successful level of income for Sahabat in AIM. As for the research methodology, or the research design, descriptive, exploratory and conclusive research will be used. For the sampling technique, stratified and simple random sample (probability sampling) will be used where the researcher will distribute 108 questionnaires to selected Sahabat. Reliability test, frequency, descriptive, correlation and regression have been used in this study to get the data from the questionnaire. Lastly, for the findings, the result shows motivation and innovation is the most effective element while goal, vision and teamwork are the least impact elements. The research also provides some recommendation to AIM to improve their elements of personal attitudes to become more effective. All the data gathered from the questionnaire will be analyzed using Statistic Package for Social Science (SPSS)version 20.0.